Strangulated diaphragmatic hernia in an elderly man - Zakaria AD,; Hayati Firdaus,; Ng, CY; Yeap, BT; Zainal Abidin ZA, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
A congenital diaphragmatic hernia is very uncommon among adults. A diaphragmatic hernia is primarily acute in onset and it is usually identified after trauma. It occurs mostly on the left side. We would like to report a 68-year-old male who presented with a 4-day history of acute intestinal obstruction with a background history of change in bowel habit for a month secondary to a right diaphragmatic hernia. He did not have any history of trauma. Clinical examination revealed a distended abdomen with high pitched bowel sound and no palpable mass. The right lung was inaudible on auscultation. Computed tomography scan was consistent with a right diaphragmatic hernia and acute intestinal obstruction. We highlight the late onset of a congenital diaphragmatic hernia and emphasize the vital need for perioperative management to ensure a promising surgical outcome.